2008
DOI: 10.1016/j.conbuildmat.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

New approach in measuring water absorption of recycled aggregates

Abstract: With the increase in the use of recycled aggregate concrete, the demand on recycled aggregate (RA) is escalating. As such, the behaviour and characteristics of RA need to be clearly understood. In practice, the testing procedures of aggregates in Hong Kong follow those laid down in British Standard Institution (BSI) (BS: 812), which provide a good foundation for assessing properties of natural aggregates. As RA may have cement paste attached that may detach from the mass during sample preparation when repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 9 publications
1
46
0
8
Order By: Relevance
“…Studies have been published that determine this property more accurately for CRA 27 . But none were found that address the problems of applying EN 1097-6 to the fine fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been published that determine this property more accurately for CRA 27 . But none were found that address the problems of applying EN 1097-6 to the fine fraction.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor absorción de los ARH se debe a la gran absorción que presenta el mortero adherido a éstos (7,(13)(14)(15) …”
Section: Composición De Los Arunclassified
“…The higher absorption on RCA is due to the high absorption of the mortar attached to it (7,(13)(14)(15). Similar results as the ones encountered have been found in different publications (7,(16)(17)(18)(19).…”
Section: Rca Compositionmentioning
confidence: 99%
“…Se observa que la granulometría de los cuatro áridos reciclados era similar al árido natural obteniéndose en todos los casos un tamaño máximo de 19 mm. Los áridos obtenidos de escombros de hormigón de peor calidad producen áridos de menor densidad y mayor porciento de absorción tal y como se esperaba de acuerdo a los resultados obtenidos por otros investigadores (26)(27)(28). Por otro lado estos tienen una forma más redondeada.…”
Section: Propiedades De Los áRidos Gruesosunclassified